Surgical strategies and outcomes of congenital supravalvular aortic stenosis. Issue 10 (1st October 2017) - Liu, Hongli; Gao, Botao; Sun, Qi; Du, Xinwei; Pan, Yanjun; Zhu, Zhongqun; He, Xiaomin; Zheng, Jinghao
Abstract: Background: Various surgical techniques have been introduced to treat supravalvular aortic stenosis (SVAS). However, there is no consensus upon the optimal approach. This study reviewed our institutional experience in the management of SVAS. Methods: Ninety patients undergoing surgery for SVAS were identified between 2009 and 2016. Based on surgical techniques, patients were divided into three groups: McGoon repair ( n  = 63), Doty repair ( n  = 24), and Brom repair ( n  = 3). Median follow‐up was 38.5 months (range, 4 months‐7.5 years). Patient status, cumulative event‐free survival rate, and risk factors for adverse clinical outcomes were assessed. Results: The early mortality rate was 3.3%. There was one late death and two reinterventions. No differences were observed among three surgical groups. Event‐free survival was 98.4% at 3 years and 96.5% at 5 years. Diffuse‐type SVAS and a preoperative gradient greater than 60 mmHg were risk factors for adverse cardiac remodeling within 6 months post‐surgery. Residual aortic stenosis was associated with male gender, preoperative aortic valve stenosis, and a preoperative peak gradient greater than 90 mmHg. Eleven patients (out of 30) who underwent concomitant pulmonary artery patching had a residual pulmonary gradient greater than 40 mmHg. Conclusions: Surgical repair of SVAS can be safely achieved using different techniques, with similar midterm mortality and reintervention rates. Higher preoperative gradient is associated with worse clinical results. Issues regarding surgical timing and concomitant pulmonary artery stenosis need to be further addressed.